PENDIOIKAN SEJARAH DAN NASIONALISME - Dyah Kumalasari (LPMPP Universitas Negeri Yogyakarta, 2008)
This article aims at reviewing how far history instruction has been ableto build nationalism spirit among the learners. Diversities of Indonesianpeople asan objective condition, especially in terms of ethnics, religions,cultures,and languages have been very susceptible to and potential causesof disintegrationof Indonesian people..History education laden withvalues of the· national struggles .for independence is considered as strategicmedia for rebuilding the nationalism spirit among the learners. Reinventingnationalism spirit among the learners ·as representatives for youthgeneration is very crucial for maintaining Indonesian integrity asanintegrated nation.